PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT. PADMA SOODE INDONESIA - Sulastri, . . (Universitas Mercu Buana, 2019)
Abstract: The purpose of this study was to examine the Effect of Leadership, Organizational Culture and Work Discipline on Performance on Employees of PT. Padma Soode Indonesia with 99 respondents as permanent employees who work at PT. Padma Soode Indonesia. Data is processed with Partial Least Square (smartPLS) version 3.0. The research design used by the author in this study was conclusive research, a type of causal research using a descriptive method with a quantitative approach. The results of this study indicate that leadership has a positive and significant effect on work discipline, organizational culture has a positive andÂ significant effect on work discipline, leadership has a positive and significant effect on performance, organizational culture has a positive effect on performance, work discipline has a positive and significant effect on performance, leadership through Work discipline as an intervening variable has a positive and significant effect on performance, and organizational culture through work discipline as an intervening variable has an effect on performance.